Philosophy in Qajar Iran - Pourjavady, Reza, (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2019)
During its Qajar period (1210-1344/1795-1925), Iran witnessed some lively and significant philosophical discourse. Yet apart from studies devoted to individual figures such as Mullā Hādī Sabzawārī and Shaykh Aḥmad Aḥsāʾī, modern scholarship has paid little attention to the animated discussions and vibrant traditions of philosophy that continued in Iran during this period. The articles assembled in this book present an account of the life, works and philosophical challenges taken up by seven major philosophers of the Qajar period. As a collection, the articles convey the range and diversity of Qajar philosophical thinking. Besides indigenous thoughts, the book also deals with the reception of European philosophy in Iran at the time.